Transformational Leadership and Nurse Performance Among Hospital Nurses - Sunardi Sunardi; Kenes Agessi (Poltekkes Kemenkes Semarang, 2026)
Background: Transformational leadership is a leadership style that inspires, motivates, and provides intellectual stimulation to nurses. Nurse performance is a critical determinant in ensuring patient safety and the quality of nursing care within hospital settings. The relationship between transformational leadership and nurse performance remains a significant issue that requires thorough examination to support improvements in the quality of nursing services. Purpose: This study aimed to analyze the relationship between transformational leadership and nurse performance in hospital setting. Methods: A total of 60 staff nurses in inpatient wards were recruited through purposive sampling. Data were collected using the Multifactor Leadership Questionnaire (MLQ) to assess transformational leadership and the Individual Work Performance Questionnaire (IWPQ) to measure nurse performance. Data analysis was conducted using Spearman’s rank correlation test. Results: A significant positive correlation of moderate strength was identified between transformational leadership and nurse performance (r = 0.488; p < 0.001), indicating that higher levels of transformational leadership are associated with better nurse performance. Conclusion: Transformational leadership demonstrates a positive, moderately strong association with nurse performance at RSI Aisyiyah Malang. Keywords: Transformational Leadership; Nurse Performance; Nursing Management; Hospital.